(a^2 - b^2)*(a - b)^2 = (a^2 - b^2) (a^2 - 2ab + b^2) = a^4 - 2a^3b + a^2b^2 - a^2b^2 + 2ab^3 - b^4 = a^4 - 2a^3b + 2ab^3 - b^4
(a^2 - b^2)^2 = a^4 - 2a^2b^2 + b^4
Нет нельзя - разные результаты при вычислениях
Нет тут формулы сокращённого умножения
Разность квадратов
И квадрат разности
Пошаговое объяснение:
(a^2 - b^2)*(a - b)^2 = (a^2 - b^2) (a^2 - 2ab + b^2) = a^4 - 2a^3b + a^2b^2 - a^2b^2 + 2ab^3 - b^4 = a^4 - 2a^3b + 2ab^3 - b^4
(a^2 - b^2)^2 = a^4 - 2a^2b^2 + b^4
Нет нельзя - разные результаты при вычислениях
Нет тут формулы сокращённого умножения
Разность квадратов![a^{2} -b^{2} =(a-b)*(a+b)](/tpl/images/0957/8236/5ab1a.png)
И квадрат разности![(a-b)^{2} =a^{2}+ b^{2} -2ab](/tpl/images/0957/8236/47c80.png)
Пошаговое объяснение: